2021
DOI: 10.7146/njlis.v2i1.125251
|View full text |Cite
|
Sign up to set email alerts
|

Samfunnsoppdrag under press

Abstract: As the Covid-19 pandemic hit the world and Norway in 2020, libraries were among the institutions that were impacted. The social mission of libraries to stay open and offer services, cultural experiences and reliable information was put under pressure. In this article we depart from a survey of 843 library workers across public, academic, special, and school libraries in Norway. The survey was conducted in June-August 2020 and contains quantitative and qualitative data on how library workers experienced lockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
1
0
5
Order By: Relevance
“…The COVID-19 lockdowns that were implemented in various ways across Scandinavia in 2020-2021 are thought to have created a situation forcing LAMs to develop new means of communicating online. However, studies of both Norwegian libraries (Evjen et al 2021) and Danish museums (Dam Christensen, Myrczik, and Roued-Cunliffe 2020) found that rather than transforming digital communication, there seems to have been an escalation of previous practice.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 lockdowns that were implemented in various ways across Scandinavia in 2020-2021 are thought to have created a situation forcing LAMs to develop new means of communicating online. However, studies of both Norwegian libraries (Evjen et al 2021) and Danish museums (Dam Christensen, Myrczik, and Roued-Cunliffe 2020) found that rather than transforming digital communication, there seems to have been an escalation of previous practice.…”
Section: Discussionmentioning
confidence: 99%
“…Folkebiblioteket inngår som del av den bredere norske bibliotekinstitusjonen med universitets-og høgskolebibliotek, skolebibliotek og Nasjonalbiblioteket (Evjen et al, 2021). Her setter jeg imidlertid fokuset på folkebiblioteket alene, med vekt på endringer over tid, og hvordan dette har skapt forutsetningene for arbeidet for baerekraftig utvikling.…”
Section: Nyinstitusjonell Organisasjonsteori Og Endring I Folkebiblio...unclassified
“…Folkebiblioteket inngår som del av den bredere norske bibliotekinstitusjonen med universitets-og høgskolebibliotek, skolebibliotek og Nasjonalbiblioteket (Evjen et al, 2021). Her setter jeg imidlertid fokuset på folkebiblioteket alene, med vekt på endringer over tid, og hvordan dette har skapt forutsetningene for arbeidet for baerekraftig utvikling.…”
Section: Nyinstitusjonell Organisasjonsteori Og Endring I Folkebiblio...unclassified